Chapter 8 The Status and Role of the alpine Cryosphere in Central Asia - Hoelzle, Martin (Taylor & Francis, 2019)
The alpine cryosphere including snow, glaciers and permafrost are critical to water management in the Aral Sea Basin (ASB) and larger Central Asia (CA) under changing climate: as they store large amounts of water in its solid forms. Most cryospheric components in the Aral Sea Basin are close to melting point, and hence very vulnerable to a slight increase in air temperature with significant consequences to long-term water availability and to water resources variability and extremes. Current knowledge about different components of cryosphere and their connection to climate in the Basin and in the entire Central Asia, varies. While it is advanced in the topics of snow and glaciers, knowledge on permafrost it rather limited. Observed trends in runoff point in the direction of increasing water availability in July and August at least until mid-century and increasing possibility for water storage in reservoirs and aquifers. However, eventually this will change as glaciers waste away. Future runoff may change considerably after mid-century and start to decline if not compensated by increasing precipitation. Cryosphere monitoring systems are the basis for sound estimates of water availability and water-related hazards associated with snow, glaciers and permafrost. They require a well-distributed observational network for all cryospheric variables. Such systems need to be re-established in the Basin after the breakup of the Soviet Union in the early 1990s. This process is slowly emerging in the region. Collaboration between local operational hydro-meteorological services and academic sector, and with international research networks may improving the observing capabilities in high mountain regions of CA Asia in general and the ASB specifically.